Informality as Experimentation: Water Utilities' Strategies for Cost Recovery and their Consequences for Universal Access. Issue 2 (1st February 2020) - Mitlin, Diana; Walnycki, Anna
Abstract: This paper considers the modalities by which utilities in four sub-Saharan African cities have extended water services into low-income settlements and examines their consequences for household access to water. We argue that water utilities and other public agencies supplying water are experimenting, drawing on the approaches of informal suppliers, to find ways to extend their coverage into low-income and/or informal neighbourhoods despite their legal status. While this experimentation appears to be extending access, prices prevent low-income households from being able to purchase sufficient quantities of water from public suppliers. Prices remain high in a context in which cost-recovery is a priority for utilities. Using a critical political economy approach, we argue that water pricing strategies applied in informal settlements present a form of accumulation enacted through the 'market integration' of low-income, primarily informal households that appears to undermine attempts to build the universal access to water services promised by Sustainable Development Goal 6.